The confusion in Peru between the collation (inheritance advance) and the imputation to the legitimate (legitimate advance) - Aliaga Castillo, Cesar A. (2011)
Within Inheritance Law, collation occupies a privileged place since it is the action aimed at balancing the hereditary quotas of forced heirs, thus remedying situations of imbalance that could be generated by the granting of liberalities inter vivos by the deceased in favor of someone of their heirs, and, to the detriment of others. In this article we will study the difference between the collation and the imputation to the legitimate or ex-se, since in our country both legal institutions are confused, which distances the collation from its own purposes and, correlatively, harms the heirs. forced. Our objective is to develop the concepts and analysis necessary for a full understanding of these legal institutions.